New first certificate Gold coursebook - Newbrook, Jacky; Wilson, Judith; Acklam, Richard (Longman, 2004)
The Gold series builds students\' confidence through carefully graded exam training and thorough language development. This new edition features 100% new content yet retains the winning formula that has made it so popular with students, whether they are aiming for exam excellence, or simply greater confidence in English.
Keywords: lingvistika, lékařská terminologie; ANGLIČTINA